A WEB based Information System for Pregnancy Women - Bin Muadhah, Eman Mohammed; Khairunnisha Zainal, Nur; Farahana Kamsin, Intan (International Journal of Psychosocial Rehabilitation, 2019)
This paper proposes Pregnancy knowledge management system website platform in which it to be controlled by gynaecology organizations. This enables the organizations to allocate and collect data of pregnant patients and their activities within the website. The main purposes of this website is to provide authenticated and certified health information within its’ search tool with collaboration of Health on the Net Foundation besides providing information like doctors posted researches, pregnancy workouts, appointments calendar, to-do list, hospital bag, provides a web-based platform for mothers and doctors to be able to interact as direct online consultation within the system. This website may be widely used by the pregnant mothers since smart phones/laptops have become common and affordable for all. Based on the user acceptance tests which were conducted, the system can be evaluated as a success. This is because the pregnancy website knowledge management system managed to fulfil the approval of mainstream users.